2022
DOI: 10.3390/nu14051122
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serum Acylcarnitines Profile after a Prolonged Stay in Intensive Care

Abstract: A stay in intensive care unit (ICU) exposes patients to a risk of carnitine deficiency. Moreover, acylated derivates of carnitine (acylcarnitines, AC) are biomarkers for metabolic mitochondrial dysfunction that have been linked to post-ICU disorders. This study aimed to describe the AC profile of survivors of a prolonged ICU stay (≥7 days). Survivors enrolled in our post-ICU clinic between September 2020 and July 2021 were included. Blood analysis was routinely performed during the days after ICU discharge, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…In the present study, LCACs were elevated in both groups compared to the reference population [ 4 ]. LCACs are also considered as markers of mitochondrial dysfunction, as increased levels are associated with the impaired mitochondrial ability of fatty acid oxidation [ 3 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In the present study, LCACs were elevated in both groups compared to the reference population [ 4 ]. LCACs are also considered as markers of mitochondrial dysfunction, as increased levels are associated with the impaired mitochondrial ability of fatty acid oxidation [ 3 ].…”
Section: Discussionmentioning
confidence: 63%
“…Inflammation is a well-known trigger for mitochondrial dysfunction [ 19 , 20 ]. Residual or persistent inflammation is typically observed early after ICU discharge [ 4 ]. Skeletal muscle, rich in mitochondria, is vulnerable to the various forms of mitochondrial alterations observed early after critical illness, thus explaining at least partly the neuromuscular failure in ICU survivors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis, which is considered a risk factor for ICU-AW, is one of the primary diseases for which CRRT is commenced in the ICU (19) ; it accounted for half of the eligible ICU cases in this study. Furthermore, recent reports have found that muscle weakness in ICU patients is due to mitochondrial dysfunction (9) , (20) . Impaired β-oxidation of fatty acids in the mitochondria may induce the accumulation of acyl-CoA and contribute to mitochondrial dysfunction (9) , (21) .…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine replacement therapy can reduce the risk of cardiac complications, anemia, muscle weakness, and other complications (6) , (7) , (8) . However, reports on the comprehensive evaluation of carnitine concentrations in critically ill patients are scarce, and carnitine deficiency in intensive care settings has not been adequately assessed (9) . Furthermore, reports of carnitine deficiency in adult patients undergoing continuous renal replacement therapy (CRRT), which is used in intensive care settings, are lacking.…”
Section: Introductionmentioning
confidence: 99%